EFEKTIVITAS PENGGUNAAN AUGMENTED REALITY (AR) PADA POP-UP BOOK INTERAKTIF TERHADAP PENINGKATAN LITERASI VISUAL DAN EMPATI - Raden Roro Maya Candra Pinata; Eka Olivia Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study presents an analysis of the effectiveness of integrating immersive Augmented Reality (AR) technology into interactive pop-up book media in improving two essential domains: visual literacy and social empathy in children aged 5-6 years at Nailil Huda Preschool. This study uses a mixed-methods design approach that combines the Research and Development (R&D) development model with the Analysis, Design, Development, Implementation, Evaluation (ADDIE) framework and a quasi-experimental quantitative method (quasi-experimental pre-test and post-test control group design). Quantitative data collection was carried out using standard instruments that have been validated and calibrated for gestational age, including a visual literacy observation instrument based on the Visual-Motor Integration (VMI) and a modified Empathy Questionnaire (EmQue) questionnaire as well as parameters from the Kids’ Empathic Development Scale (KEDS) to measure cognitive, affective, and prosocial behavioral tendencies. The results of comparative statistical analysis and significance tests showed a very dramatic and statistically significant increase in the experimental group. Children's visual literacy skills, including symbol understanding, object description, and story-retelling, experienced an average increase of 26.20%, with the highest improvement in the ability to describe images in detail and spatial memory retention. Meanwhile, empathy and social skills competency scores, encompassing perspective-taking, active caring, and nonviolent conflict resolution, experienced a massive increase of 49.40% when compared to the control group exposed to conventional two-dimensional (2D) picture book narratives.